Stable oxygen and carbon isotope record of upper Maestrichtian to lower Eocene benthic foraminifera - Koji Seto; Ritsuo Nomura; Nobuaki Niitsuma (PANGAEA, 1991)
Oxygen and carbon isotope ratios of benthic foraminifers were measured on the continuous middle to lower bathyal sedimentary sequence dated from the upper Maestrichtian to lower Eocene which was recovered at Site 752 in the eastern Indian Ocean. The changes in the carbon isotope values can be correlated with the faunal changes of the benthic foraminifers.
Supplement to: Seto, K et al. (1991): Data report: oxygen and carbon isotope records of the upper Maestrichtian to lower Eocene benthic foraminifers at Site 752 in the eastern Indian Ocean. In: Weissel, J; Peirce, J; Taylor, E; et al. (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 121, 885-889, https://doi.org/10.2973/odp.proc.sr.121.184.1991